2018
DOI: 10.1139/apnm-2017-0505
|View full text |Cite
|
Sign up to set email alerts
|

No effect of acute normobaric hypoxia on plasma triglyceride levels in fasting healthy men

Abstract: Circulating fatty acids are a major systemic energy source in the fasting state as well as a determinant of hepatic triglycerides (TG)-rich very-low-density lipoprotein production. Upon acute hypoxia, sympathetic arousal induces adipose tissue lipolysis, resulting in an increase in circulating nonesterified fatty acids (NEFA). Animal studies suggest that TG clearance may also be strongly reduced under hypoxia, though this effect has been shown to be dependent on temperature. Whether the hypoxia-induced rise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
14
2
Order By: Relevance
“…Because we thought that the postprandial rise in insulin might have inhibited adipose tissue lipolysis and suppressed hepatic very-low density lipoprotein (VLDL) production, we conducted another study in the fasting state under continuous (i.e., not intermittent) hypoxic conditions. Again, we observed no effect of hypoxia on circulating TG (Mahat et al, 2018). Interestingly, despite no changes in plasma TG concentrations, our previous studies reported significant increases (∼+35%) in circulating non-esterified fatty acids, which is an important contributor to hepatic lipogenesis and very-low density lipoprotein production (Nielsen and Karpe, 2012).…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Because we thought that the postprandial rise in insulin might have inhibited adipose tissue lipolysis and suppressed hepatic very-low density lipoprotein (VLDL) production, we conducted another study in the fasting state under continuous (i.e., not intermittent) hypoxic conditions. Again, we observed no effect of hypoxia on circulating TG (Mahat et al, 2018). Interestingly, despite no changes in plasma TG concentrations, our previous studies reported significant increases (∼+35%) in circulating non-esterified fatty acids, which is an important contributor to hepatic lipogenesis and very-low density lipoprotein production (Nielsen and Karpe, 2012).…”
Section: Introductioncontrasting
confidence: 53%
“…While the regulation of VLDL and chylomicron remnants uptake is still poorly understood (Ramasamy, 2013), VLDL production is generally accepted to be reduced in the postprandial state, mainly because insulin inhibits adipose tissue lipolysis, thus reducing hepatic NEFA delivery, the main substrate for VLDL-TG production (Nielsen and Karpe, 2012). In our previous study conducted in the fasted state, the increase in circulating NEFA under hypoxia was not matched by an increase in plasma TG concentration, suggesting that in the fasted state, increased availability of NEFA alone may not acutely affect hepatic VLDL production (Mahat et al, 2018). In the present study, however, it could be suspected that the combination of chylomicron remnants delivery and elevated plasma NEFA may have provided enough lipid substrate to drive an increase in hepatic VLDL production.…”
Section: Discussionmentioning
confidence: 95%
“…One possible explanation is that, under exposure to hypoxia, the upregulated HIF could increase the expression of the lipoprotein lipase gene through PPARc1 to prevent the loss of HDL-C [62]. Furthermore, we observed the higher magnitude of elevated serum FFA after LHTHL in the fasting state even with a decrease in serum TG, which is concordant with Mahat's report [63]. In previous studies, it has been demonstrated that the substrate shifts from carbohydrates to lipids for the energy source during the postexercise recovery period [64].…”
Section: Discussionsupporting
confidence: 92%
“…Two other findings pertain to reduced metabolic effects of acute hypoxia in the newborns of the present study. We did not see an increase in plasma triglycerides levels, akin to findings during acute hypoxia in humans (59). In addition, we did not see changes in plasma oxidative stress markers in response to acute hypoxia.…”
Section: Discussioncontrasting
confidence: 52%